Penularan Penyakit CVPD (Citrus Vein Phloem Degeneration) oleh Diaphorina citri Kuwayama (Homoptera: Psyllidae) pada Tanaman Jeruk Siam - WIJAYA, I NYOMAN (AGRITROP, 2012)
The desperation rate of CVPD disease on the central of citrus area in Bali were 32% per year, however the populations of D. citri as vector were relative low, so that the research concerning on the minimum population of D. citri that effective as vector were needed. The aims of this research were to know the minimum population of D. citri to transmit CVPD effectively, incubation periods of disease on citrus siam variety and the characteristic of pathogen on the vector. The research was carried out in the glass house of Department Plant Pest and Disease, Faculty of Agriculture Udayana University. The result showed that transmission of CVPD disease could be infected by one imago of D. citri, through the increase of vector population decreased the infection period of CVPD diseased. Liberobacter asiaticum as the pathogen of CVPD had ability to persistent on the vector.
Keywords: D. citri, incubation period, persistent, CVPD, citrus